High-strength, highly formable steel plate with excellent spot weldability and manufacturing method thereof

A high-strength steel with controlled microstructure and manufacturing process addresses the balance of strength and formability, enhancing weldability by reducing LME susceptibility through specific alloying and controlled rolling.

JP2025501537APending Publication Date: 2025-01-22POHANG IRON & STEEL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024536514
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-21
Filing Date
2022-12-19
Publication Date
2025-01-22

AI Technical Summary

Technical Problem

Existing high-strength steels face challenges in achieving a balance between strength and formability, particularly in preventing liquid metal embrittlement (LME) during spot welding, which leads to cracking and poor weldability.

Method used

A steel composition with controlled microstructure and manufacturing process, including specific alloying elements (C, Si, Mn, Ti, Nb, Cr, P, S) and controlled hot and cold rolling, followed by annealing, to create a sound surface layer with a balanced microstructure of soft and hard phases, reducing LME susceptibility.

Benefits of technology

The solution provides high-strength steel with excellent formability and improved spot weldability, preventing processing defects like cracks and wrinkles, suitable for complex-shaped structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501537000001_ABST
    Figure 2025501537000001_ABST
Patent Text Reader

Abstract

The present invention relates to a steel sheet for use in automobiles and the like, and relates to a steel sheet having not only high strength and high formability but also excellent spot weldability, and a manufacturing method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel sheet for use in automobiles and the like, and relates to a steel sheet having not only high strength and high formability but also excellent spot weldability, and a manufacturing method thereof. [Background technology]

[0002] Improving fuel efficiency and durability are important issues that automobile companies must solve. To achieve this, the use of thin, high-strength steel can simultaneously improve various issues such as the environment, fuel efficiency, crashworthiness, and durability. For example, the Insurance Institute for Highway Safety in the United States has gradually strengthened crash stability regulations for passenger protection, and since 2013 has required strict crash components such as a 25% small overlap. One solution to this problem is to reduce the weight of automobiles, which requires high strength steel materials as well as high formability.

[0003] However, while higher steel strength has the advantage of absorbing impact energy, generally higher strength leads to lower elongation and poor formability. In addition, if the yield strength is too high, the flow of material into the die during forming is reduced, resulting in poor formability. Therefore, the automotive industry is calling on the steel industry to develop steel that has excellent strength and formability, i.e., a good balance between strength and elongation (TS*El).

[0004] To meet these demands, steel companies are developing various products, such as dual phase steel (DP steel), transformation induced plasticity steel (TRIP steel), complex phase steel (CP steel), and ferrite-bainite steel (FB steel), which are manufactured through processes of wire making, steel making, continuous casting, hot rolling, cold rolling, and annealing.

[0005] In order to ensure such strength and formability, the amount of alloying elements added to steel materials is often increased, and in this case, defects may occur during spot welding to manufacture automotive parts. Spot welding is the most common joining process in the manufacture of automotive parts, and is the most widely used method because it is low cost and has excellent productivity.

[0006] In order to ensure the corrosion resistance of steel materials, they are often plated. Zinc-plated steel sheets in particular have excellent corrosion resistance and formability, but they can suffer from liquid metal embrittlement (LME). Liquid metal embrittlement is a phenomenon in which brittleness occurs when a ductile material comes into contact with liquid metal, and in the presence of tensile stress, the liquid metal rapidly penetrates along the grain boundaries of the base material, causing brittleness.

[0007] Generally, welding such as spot welding is widely used as a method for joining automotive parts. However, during welding, the temperature of the heat-affected zone of the material rises, causing the coating layer to melt, and tensile stress is generated by electrode pressure, which can cause cracks due to liquid metal embrittlement. In particular, when galvanized steel sheets are spot welded, the molten zinc, which has a low melting point, can cause liquid metal embrittlement cracks in the welded parts.

[0008] Therefore, there is a demand for technology that can ensure excellent strength and formability while improving spot weldability to resolve defects caused by liquid metal embrittlement (LME). Summary of the Invention [Problem to be solved by the invention]

[0009] An aspect of the present invention is to provide a steel plate having excellent strength and formability while at the same time having excellent spot weldability, and a method for manufacturing the same.

[0010] The object of the present invention is not limited to the above. Further object of the present invention is described in the entire contents of the specification, and a person having ordinary skill in the art to which the present invention pertains will have no difficulty in understanding the further object of the present invention from the contents described in the specification of the present invention. [Means for solving the problem]

[0011] One aspect of the present invention is a steel sheet having, by weight percent, C: 0.05 to 0.10%, Si: 0.3% or less (excluding 0), Mn: 2.0 to 2.5%, Ti: 0.05% or less (excluding 0), Nb: 0.1% or less (excluding 0), Cr: 1.5% or less (excluding 0), P: 0.1% or less, S: 0.01% or less, and the remainder including Fe and unavoidable impurities, The microstructure at 1 / 4 of the steel plate thickness (t) contains 65-85% soft phase by area fraction, with the remainder being hard phase. The present invention relates to a high-strength, highly formable steel plate having excellent spot weldability, which includes a sound layer in the surface layer portion of the steel plate, the sound layer having a thickness of 5 to 50 μm.

[0012] Another aspect of the present invention is a process for heating a steel slab containing, by weight, C: 0.05-0.10%, Si: 0.3% or less (excluding 0), Mn: 2.0-2.5%, Ti: 0.05% or less (excluding 0), Nb: 0.1% or less (excluding 0), Cr: 1.5% or less (excluding 0), P: 0.1% or less, S: 0.01% or less, and the remainder being Fe and unavoidable impurities, at a temperature range of 1100-1300°C; hot rolling the heated steel slab, and hot rolling the steel slab while cooling the steel slab so that the surface temperature of the steel slab is Ar3 or less for a predetermined time during finish hot rolling; coiling and cooling the hot-rolled sheet; cold rolling the cooled hot rolled sheet at a rolling reduction of 70 to 90%; After the cold rolling, heating to a temperature range of Ac1 to Ac1+30° C. and maintaining the temperature; and cooling the cold-rolled steel sheet slowly to a temperature range of 650 to 700°C at an average cooling rate of 1 to 10°C / s, and then quenching the cold-rolled steel sheet to a temperature range of 300 to 580°C at an average cooling rate of 5 to 50°C / s; The present invention relates to a method for producing a high-strength, highly formable steel plate having excellent spot weldability, comprising: Effect of the Invention

[0013] According to the present invention, it is possible to provide a steel sheet having high strength and formability, especially an excellent balance between strength and ductility (TS*El), which can prevent processing defects such as cracks or wrinkles during press forming, and therefore can be suitably applied to structural parts that require processing into complex shapes. In addition, it is possible to improve product quality by improving spot weldability and reducing the occurrence of liquid metal embrittlement (LME).

[0014] The various yet significant advantages and effects of the present invention are not limited to the above, but can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]

[0015] [Figure 1] 1 is a drawing showing cracks that occur during spot welding of a galvannealed steel sheet. [Diagram 2] 1 is a photograph showing an observation of a surface layer portion of a steel sheet in Example 1 among the examples of the present invention. [Diagram 3] 1 is a photograph showing an observation of a surface layer portion of a steel sheet in Comparative Example 1 among the examples of the present invention. [Figure 4] FIG. 2 is a schematic diagram illustrating an example of a method for measuring the aspect ratio of a hard phase. [Diagram 5] 1 is a graph showing a change in material temperature when water cooling is applied and not applied during finish hot rolling in the present invention. [Figure 6] 1 is a graphical representation of the heat treatment steps of a continuous annealing process. [Figure 7] 1 is a photograph showing cracks caused by LME observed after completion of spot welding in Comparative Example 1 among the examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The terms used in this specification are for the purpose of describing the present invention and are not intended to limit the present invention. Furthermore, the singular forms used in this specification include the plural forms unless the relevant definition clearly indicates otherwise.

[0017] The meaning of "comprise" as used in the specification is to specify a feature and does not exclude the presence or addition of other features.

[0018] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Dictionary-defined terms are to be interpreted to have a meaning consistent with the relevant technical literature and the presently disclosed content.

[0019] In order to ensure strength and formability, typical high-strength steels used as automotive materials include dual phase steel (DP steel), transformation induced plasticity steel (TRIP steel), complex phase steel (CP steel), ferrite-bainite steel (FB steel), etc. These high-strength steels generally have high alloys, and such high-alloy galvanized high-strength steels may cause cracks due to liquid metal embrittlement (LME) during spot welding.

[0020] The causes of the above LME include loads above the critical limit, molten metal, and the appearance of austenite. When spot welding, the temperature of the steel rises due to resistance heat as current is applied, and zinc, which has a low melting point, begins to melt first. After that, the steel transforms into austenite, and the lower the austenite formation temperature, the longer the time that the molten zinc and the austenite structure of the steel are in contact with each other at the surface. When thermal stress or external stress is applied at this time, the austenite grain boundaries in the area where the stress is concentrated begin to slide and deform. If the interfacial energy between the steel and molten zinc is lower than the austenite grain boundary energy, the molten zinc penetrates the austenite grain boundaries, causing grain boundary cracking. This ultimately leads to a deterioration of spot weldability. Figure 1 shows the cracks that appear when welding a commercially available 1200MPa-class galvannealed high-strength steel.

[0021] In order to eliminate the above-mentioned weld cracks caused by LME, methods such as austenite suppression, molten metal restriction, and external stress restriction are being discussed.

[0022] However, since the welding temperature rises to the melting point, it is not easy to prevent the appearance of austenite in steel. On the contrary, the A3 temperature decreases as the amount of alloying elements such as C and Mn increases. Therefore, since austenite can appear at a lower temperature in high-strength steel, cracking due to LME occurs more easily.

[0023] Meanwhile, in the case of zinc plating, it is possible to consider increasing the melting temperature of zinc or reducing the plating thickness to reduce the amount of molten zinc, but this would result in a decrease in corrosion resistance and workability of the steel sheet, as well as an increase in plating costs, etc.

[0024] Reducing external stress is not easy because it involves the joint strength and quality of the welded parts.

[0025] The above-mentioned methods cannot sufficiently suppress microcracks caused by LME. Therefore, the inventors have studied the above-mentioned cracks caused by LME and, fortunately, have found that LME during spot welding is a phenomenon that occurs in the surface layer of a steel sheet. They have recognized that it is possible to reduce LME and improve spot weldability by changing the material of the surface layer of a steel sheet, thereby ensuring excellent strength and formability, and have arrived at the present invention.

[0026] The present invention will be described in detail below. First, an embodiment of the steel sheet of the present invention will be described in detail.

[0027] The alloy composition of the steel plate of the present invention is, in weight percent, C: 0.05-0.10%, Si: 0.3% or less (excluding 0), Mn: 2.0-2.5%, Ti: 0.05% or less (excluding 0), Nb: 0.1% or less (excluding 0), Cr: 1.5% or less (excluding 0), P: 0.1% or less, S: 0.01% or less, and the remainder includes Fe and inevitable impurities. The above alloy composition is described in detail below. Unless otherwise specified in the present invention, the content of each element is based on weight percent.

[0028] Carbon (C): 0.05~0.10% The C is an important element added for solid solution strengthening, and this C combines with precipitate elements to form fine precipitates, thereby contributing to improving the strength of the steel. If the C content exceeds 0.10%, the hardening ability increases, and as martensite is formed during cooling during steel manufacturing, the strength increases excessively, but the elongation rate may decrease. In addition, the weldability may deteriorate, and welding defects may occur during processing into parts. If the C content is less than 0.05%, it may be difficult to ensure the target level of strength. More preferably, it is 0.06 to 0.08%.

[0029] Silicon (Si): 0.3% or less (excluding 0) The above-mentioned Si is a ferrite stabilizing element, and is advantageous in securing the target level of ferrite fraction by promoting ferrite transformation. In addition, it has excellent solid solution strengthening ability, is effective in increasing the strength of ferrite, and is a useful element in securing strength without reducing the ductility of steel. If the above-mentioned Si content exceeds 0.3%, the effect of solid solution strengthening becomes excessive, and ductility decreases, and surface scale defects are induced, adversely affecting the plating surface quality and inhibiting chemical conversion treatability. More advantageously, it is preferable that the content is 0.1% or less.

[0030] Manganese (Mn): 2.0-2.5% The Mn element is advantageous in preventing hot embrittlement caused by the formation of FeS by precipitating sulfur (S) in steel as MnS and solid-solution strengthening the steel. If the Mn content is less than 2.0%, not only will the above effects not be obtained, but it will also be difficult to ensure the target level of strength. On the other hand, if the Mn content exceeds 2.5%, problems such as weldability and hot rolling are likely to occur, and at the same time, ductility may decrease as martensite is more easily formed due to increased hardening ability. In addition, there is a problem that Mn-bands are excessively formed in the structure, increasing the risk of defects such as processing cracks. And there is a problem that Mn oxide dissolves on the surface during annealing and greatly impairs galvanic properties. More advantageously, the Mn content is preferably 2.2 to 2.4%.

[0031] Titanium (Ti): 0.05% or less (excluding 0) The Ti contributes to ensuring yield strength and tensile strength as an element that forms fine carbides. In addition, Ti has the effect of precipitating N in steel as TiN and suppressing the formation of AlN from Al that is inevitably present in steel, and has the effect of reducing the possibility of cracks occurring during continuous casting. If the Ti content exceeds 0.05%, coarse carbides will precipitate, and there is a risk of strength and elongation decreasing due to the reduction in the carbon content in the steel. In addition, there is a problem that nozzle clogging may be induced during continuous casting, increasing the manufacturing cost. Therefore, the Ti content is preferably 0.05% or less, and more preferably 0% or more.

[0032] Niobium (Nb): 0.1% or less (excluding 0) The above-mentioned Nb is an element that segregates at the austenite grain boundaries, suppresses the coarsening of austenite crystal grains during annealing heat treatment, and forms fine carbides to contribute to improving strength. If the content of Nb exceeds 0.1%, coarse carbides precipitate, and the strength and elongation may deteriorate due to the reduction of carbides in the steel, resulting in a problem of increased manufacturing costs. The above-mentioned Nb is preferably 0.1% or less, and more preferably 0% or more.

[0033] Chromium (Cr): 1.5% or less (excluding 0) The Cr element facilitates the formation of bainite, inhibits the formation of martensite during annealing heat treatment, and forms fine carbides, thereby contributing to improved strength. If the Cr content exceeds 1.5%, excessive bainite is formed, reducing elongation, and if carbides are formed at grain boundaries, strength and elongation may be deteriorated, resulting in increased manufacturing costs. Therefore, the Cr content is preferably 1.5% or less, and more preferably 0% or more.

[0034] Phosphorus (P): 0.1% or less The above P is a substitutional element with the greatest effect of solid solution strengthening, and is an element advantageous in improving in-plane anisotropy and ensuring strength without significantly reducing formability. However, if the above P is added in excess, there is a problem that the possibility of brittle fracture increases significantly, increasing the possibility of plate breakage of the slab during hot rolling, and impairing the coating surface properties. Therefore, the content of the above P is preferably 0.1% or less, and 0% can be excluded in consideration of the level of unavoidable inclusion.

[0035] Sulfur (S): 0.01% or less The above-mentioned S is an element that is inevitably added as an impurity element in steel, and since it impairs ductility, it is preferable to control its content as low as possible. In particular, since S has the problem of increasing the possibility of generating red shortness, it is preferable to control its content to 0.01% or less. However, 0% can be excluded in consideration of the level of unavoidable inclusion.

[0036] The remainder includes iron (Fe), and cannot be excluded because unintended impurities are inevitably mixed in from raw materials or the surrounding environment during normal manufacturing processes. Since these impurities are obvious to anyone with ordinary skill in the art during manufacturing processes, the contents of all of them are not specifically mentioned in this specification.

[0037] Usually, the microstructure of a steel sheet is observed at 1 / 4t (1 / 4 position of the steel sheet thickness (t)) in the thickness direction, and this is used as a reference when explaining physical properties such as strength and formability. In the present invention, the LME characteristics generated by the surface microstructure of the steel sheet and the internal microstructure that determines physical properties such as strength are explained, and the microstructure of the surface layer and the internal microstructure are explained separately. Here, the internal microstructure refers to the microstructure at 1 / 4t, and unless otherwise specified, the microstructure refers to the internal microstructure. The phase of the microstructure of steel immediately after rolling is determined depending on whether the temperature at which rolling proceeds is the austenite phase or the ferrite phase, and then the final microstructure is formed as transformation occurs depending on the cooling conditions. The hot rolling process is a stage where dynamic recrystallization occurs during rolling, and the microstructure immediately after rolling is a recrystallized austenite single phase structure when the rolling temperature is high, a recrystallized austenite / ferrite mixed phase when the rolling temperature is low, and a ferrite single phase when the temperature is very low.

[0038] Therefore, when the rolling temperature is different in the thickness direction of a steel sheet, different microstructures are obtained in the thickness direction, and when a special treatment such as spraying water during rolling is performed, it is possible to adjust the temperature only in the surface layer, thereby making the microstructure of the surface layer different. Thus, one realization idea of ​​the present invention relates to a technology for controlling the internal microstructure to ensure strength and formability, and controlling the microstructure of the surface layer to improve LME.

[0039] Hereinafter, the steel sheet includes a sound layer in a surface layer portion. The sound layer is a ferrite main structure consisting of ferrite at an area fraction of 95% or more, and it is effective that the crystal grains of the ferrite have a size of 6 to 20 μm.

[0040] On the other hand, it is effective that the thickness of the healthy layer is 5 to 50 μm. If the healthy layer in the surface layer is less than 5 μm, it is difficult to improve LME, and if it exceeds 50 μm, it is difficult to fully achieve physical properties such as the strength of the steel sheet. Figures 2 and 3 show the observations of the surface layer of Example 1 and Comparative Example 1 in the examples described later, respectively. In Figure 2, a healthy layer having coarse crystal grains was confirmed in the surface layer, but this cannot be observed in Figure 3.

[0041] The microstructure of the steel sheet (at 1 / 4 of the steel sheet thickness (t)) is composed of a hard phase and a soft phase, and it is preferable that the ferrite recrystallization is maximized by an optimized annealing process, so that the final recrystallized ferrite matrix contains a structure in which the hard phases of bainite and martensite are uniformly distributed. In the microstructure, the hard phase refers to a phase that is mainly martensite and contains a small amount of bainite, and the soft phase refers to a ferrite phase. With regard to the deformation characteristics of a structure composed of a soft phase and a hard phase, the soft phase determines the formability, and the hard phase determines the strength.

[0042] The hard phase is preferably contained in an area fraction of 15 to 35%. If the hard phase fraction is too high, the strength is high but the elongation is low, whereas if the soft phase fraction is high, the elongation is high but the strength is low. In order to ensure a strength of 780 MPa or more provided by the present invention, the hard phase is preferably contained in an area fraction of 15% or more, and preferably does not exceed 35% in order to ensure formability.

[0043] In order to ensure appropriate strength and formability at the same time, the soft phase is preferably 65 to 85% in terms of area fraction. The ferrite of the soft phase can be divided into recrystallized ferrite and non-recrystallized ferrite. The difference between recrystallized ferrite and non-recrystallized ferrite can be divided by the aspect ratio of the grain size to the rolling direction, as shown in FIG. 4. Non-recrystallized ferrite has a large aspect ratio as shown in FIG. 4(b), and when analyzed in detail, linear deformation structures are observed within the ferrite grains. On the other hand, since recrystallized ferrite is advantageous for ensuring formability, it is preferable that the recrystallized ferrite of the soft phase is 60% or more, and non-recrystallized ferrite is a soft phase, but since a high fraction reduces formability, it is preferable that the fraction is 5% or less.

[0044] On the other hand, the aspect ratio of the hard phase is preferably 1.2 or less. The aspect ratio means the ratio (b / a) of the long axis (b) and the short axis (a) of the crystal grain size in the rolling direction, as shown in (a) and (b) of FIG. 4, and the aspect ratio of the hard phase is the aspect ratio of the structure formed by stretching the hard phase in the rolling direction. If the aspect ratio of the hard phase increases, it adversely affects bending, which is important for deformation resistance in the thickness direction. In addition, if the aspect ratio of the hard phase increases, it reduces the hole expandability. Therefore, it is important to control the aspect ratio of the hard phase as low as possible, so it is preferable that it does not exceed 1.2.

[0045] The steel sheet of the present invention has a high strength of tensile strength (TS) of 780 MPa or more and an elongation of 18% or more, and therefore can ensure excellent strength and formability.

[0046] Meanwhile, the steel sheet of the present invention may further include a plating layer for improving corrosion resistance, for example, a zinc-based plating layer. Steel sheets for automobiles can be mainly formed by hot-dip plating and electroplating on a base steel sheet, and the present invention relates to a technology that can include both a plating layer formed by hot-dip plating and a plating layer formed by electroplating. The thickness of the plating layer can be varied as necessary, and may be, for example, 10 μm or less.

[0047] Next, one embodiment of the method for manufacturing a steel sheet according to the present invention will be described in detail. The steel sheet according to the present invention can be manufactured by first preparing a steel slab, heating it, hot rolling it, coiling it, cooling it, cold rolling it, and annealing it. Meanwhile, if necessary, the method can further include a process for forming a coating layer. In particular, in the present invention, in order to form a sound layer in the surface layer, hot rolling is controlled, and after deformation by cold rolling, an appropriate structure is formed in the annealing process. Each step will be described in detail below.

[0048] Steel slab heating A steel slab containing the above-mentioned alloy composition, i.e., by weight percent, C: 0.05-0.10%, Si: 0.3% or less (excluding 0), Mn: 2.0-2.5%, Ti: 0.05% or less (excluding 0), Nb: 0.1% or less (excluding 0), Cr: 1.5% or less (excluding 0), P: 0.1% or less, S: 0.01% or less, and the remainder being Fe and inevitable impurities, is prepared and then heated. This is for smoothly carrying out the subsequent hot rolling process and ensuring the target physical properties of the steel sheet, and the conditions of the heating process are not particularly limited, and may be any method and conditions normally used in the technical field to which the present invention belongs. As an example, it is preferable to heat the slab at a temperature range of 1100 to 1300°C.

[0049] Hot rolling The heated steel slab is hot-rolled to produce a hot-rolled steel sheet. In the present invention, a method for obtaining a suitable surface layer is proposed in which the temperatures of the surface and the 1 / 4 thickness position of the steel slab are differentiated during hot rolling.

[0050] For this reason, it is preferable to perform the finish hot rolling at a temperature in the center (1 / 4 thickness position), i.e., the temperature of the material itself, in the temperature range of Ar3 to 1000°C, and to perform the finish hot rolling so that the surface temperature of the material is Ar3 or less for a predetermined time during the finish hot rolling. If the outlet temperature of the material itself during the finish hot rolling is less than Ar3, the strength of the material increases and the hot deformation resistance during rolling increases rapidly, and if it exceeds 1000°C, the rolling load is relatively reduced, which is advantageous for productivity, but there is a possibility that a thick oxide scale is generated and defects are formed in the surface layer. More preferably, the finish hot rolling can be performed in the temperature range of 760 to 940°C.

[0051] Meanwhile, the surface temperature of the material is an important process for forming a sound layer at the surface layer, and the surface temperature is set to Ar3 or less so that ferrite can be easily formed by recrystallization during hot rolling, and excessive rolling load is not generated at the 1 / 4 thickness position. That is, rolling is performed simultaneously so that the surface temperature is set to Ar3 or less for a predetermined time, and ferrite can be recrystallized at the surface layer to form a sound layer of coarse ferrite. There is no particular limitation on the method for setting the surface temperature to Ar3 or less, but as an example, a method of spraying water during or between rolling passes to set the surface temperature to Ar3 or less for a predetermined time can be applied.

[0052] Figure 5 shows a time-temperature graph of hot rolling in which water cooling is applied to keep the surface temperature below Ar3 as in the present invention, and in which it is not applied. In Figure 5, it can be seen that when water cooling is not applied, the center and the surface are all rolled at a temperature above Ar3, but when water cooling is applied, the surface temperature drops to below Ar3 within a certain time.

[0053] Winding and cooling The hot-rolled steel sheet produced by the hot rolling can be wound into a coil. The winding can be performed at a temperature range of 400 to 700°C. If the winding temperature is less than 400°C, excessive martensite or bainite is formed, resulting in an excessive increase in strength of the hot-rolled steel sheet, which may cause problems such as defective shape due to the load during the subsequent cold rolling. On the other hand, if the winding temperature exceeds 700°C, surface scale may increase, resulting in deterioration of pickling properties.

[0054] Meanwhile, it is preferable to cool the coiled hot-rolled steel sheet to room temperature at an average cooling rate of 0.1°C / s or less (excluding 0). The coiled hot-rolled steel sheet may be cooled after being transported, stacked, etc., and the process before cooling is not limited thereto. By cooling the coiled hot-rolled steel sheet at a constant rate, a hot-rolled steel sheet in which carbides that become austenite nucleation sites are finely dispersed can be obtained.

[0055] Thereafter, a process of removing surface scale by pickling the surface of the hot-rolled steel sheet before the subsequent cold rolling may be further performed. The pickling method is not particularly limited, and may be a method commonly used in the technical field to which the present invention pertains.

[0056] Cold rolling The hot-rolled steel sheet coiled as described above can be cold-rolled at room temperature with a constant rolling reduction to produce a cold-rolled steel sheet.

[0057] The cold rolling is preferably performed at a reduction of 70 to 90%. If the reduction of the cold rolling is less than 70%, the driving force for recrystallization is reduced, ferrite is formed coarsely, and austenite formation is also reduced, so that the austenite fraction can be sufficiently secured by increasing the soaking temperature of the annealing furnace. On the other hand, if the cold rolling reduction exceeds 90%, there is a high possibility that cracks will occur at the edge of the steel sheet, and the initial thickness before rolling must be excessively thick, which increases the number of rolling passes and reduces productivity.

[0058] The present invention does not particularly limit the method of performing the cold rolling, and any method that is performed in the technical field to which the present invention belongs can be applied. For example, there are a TCM (Tandum Cold Rolling Mill) method and a ZRM (Sendzimir Rolling Mill) method. To explain these methods briefly, TCM is a reversible rolling method, and has the advantage of being excellent in productivity because the manufacturing cost is low and mass production is possible, but has the disadvantage of being somewhat restricted in applying a rolling force. ZRM is a reversible batch type, and has the disadvantage of being low in productivity, but has the advantage of being somewhat easy in applying a rolling force.

[0059] The reduction ratio of the cold rolling is an important operational factor for improving various physical properties by improving phase transformation of steel, and therefore, controlling the reduction ratio is particularly important for ensuring quality. In the present invention, it is preferable to adopt an appropriate method in consideration of the product material, size, operating environment, etc.

[0060] Continuous Annealing It is preferable to continuously anneal the cold rolled steel sheet thus manufactured. The continuous annealing process may be performed, for example, in a continuous annealing furnace (CAL). An example of the heat treatment steps of the continuous annealing process is shown in the graph of FIG. 6. As shown in FIG. 6, the heat treatment steps in the annealing furnace may include a heating section (HS), a soaking section (SS), a slow cooling section (SCS), a rapid cooling section (RCS), and an over aging section (OAS). In general, the temperature of each section is measured at the end of each section, so the temperature means the temperature at the end of each section. For example, the rapid cooling section (RCS) temperature is the temperature of the section where the rapid cooling section ends, and is represented as 4 in FIG. 6.

[0061] In the heating zone (HS), the steel sheet is heated at a constant heating rate, and as the temperature of the steel sheet increases, potential recovery, cementite precipitation, ferrite recrystallization, and reverse transformation in the two-phase region occur. The threading speed varies depending on the thickness and width of the steel sheet, and the microstructural changes in each temperature range may vary depending on the initial hot rolling structure and cold rolling reduction rate.

[0062] When entering the soaking zone (SS), a constant temperature is maintained for a certain period of time, during which austenite reverse transformation into two-phase or single-phase regions is observed depending on the annealing temperature. The soaking zone (SS) is known to be one of the zones that consume the most energy in an annealing furnace. In the slow cooling zone (SCS), the material is usually cooled at a low cooling rate, and after the SCS, the rapid cooling zone (RCS) is continuously cooled at a high cooling rate, and bainite may be generated during cooling depending on the RCS set temperature and hardening ability.

[0063] The temperature of the soaking zone (SS) is closely related to phase transformation. Factors that affect phase transformation and material state change include temperature, pressure, composition, etc., and when the composition is determined, it can be adjusted through temperature and pressure. In particular, the higher the temperature and pressure, the faster the phase transformation during heating in the annealing furnace can proceed, but the higher the temperature, the higher the energy cost and the higher the carbon emissions such as carbon dioxide after combustion, which is not environmentally friendly. In the steel manufacturing process, the variable that is compared with pressure is the cold reduction rate, and if the cold reduction rate is increased at the same temperature, the phase transformation proceeds faster, and in the opposite concept, if the cold reduction rate is increased, phase transformation can be achieved even at a low temperature. Using this principle, in the present invention, the cold reduction rate is set to 70 to 90%, which is higher than the conventional method.

[0064] The soaking zone temperature in a conventional annealing process is generally in the range of Ac1+30°C to Ac3-30°C. However, as described above, in the present invention, ferrite recrystallization and austenite formation are possible even when heat treatment is performed at a low temperature with a high cold rolling reduction, so it is preferable to heat to and maintain a temperature range of Ac1 to Ac1+30°C in the annealing process of the present invention. Even in the above temperature range, the present invention can improve workability by reducing hardness through recrystallization and phase transformation phenomena.

[0065] The cold-rolled steel sheet heat-treated in the above temperature range can be cooled to form a target structure, and stepwise cooling is preferably performed. In the present invention, the stepwise cooling can be performed in a slow cooling zone (SCS) and a rapid cooling zone (RCS). For example, it is preferable to perform slow cooling at an average cooling rate of 1 to 10°C / s to a temperature range of 650 to 700°C, and then rapid cooling at an average cooling rate of 5 to 50°C / s to a temperature range of 300 to 580°C. By slowing down the cooling rate during slow cooling, it is possible to suppress sheet defects caused by a sudden drop in temperature during subsequent rapid cooling.

[0066] If the end temperature of the slow cooling is less than 650°C, the carbon diffusion activity is low due to the low temperature, and the carbon concentration in the ferrite increases, while the carbon concentration in the austenite decreases, and the fraction of the hard phase becomes excessive, increasing the yield ratio and increasing the tendency for cracks to occur during processing. In addition, the temperature difference from the soaking zone becomes too large, which may cause a problem of uneven plate shape. If the end temperature exceeds 700°C, there is a disadvantage that an excessively high cooling rate is required during subsequent cooling (quenching). In addition, if the average cooling rate during the slow cooling exceeds 10°C / s, carbon diffusion cannot occur sufficiently, and it is preferable to cool at an average cooling rate of 1°C / s or more in consideration of productivity.

[0067] After the slow cooling is completed, rapid cooling is performed. If the rapid cooling end temperature is less than 300°C, cooling deviation occurs in the width and length directions of the steel sheet, which may cause deterioration of the sheet shape, and if it exceeds 580°C, the hard phase may not be sufficiently secured, resulting in low strength. On the other hand, if the average cooling rate during the rapid cooling is less than 5°C / s, the fraction of the hard phase may be excessive, and if it exceeds 50°C / s, the hard phase may be insufficient.

[0068] Meanwhile, in the annealing process, after the cooling is completed, overaging treatment (OAS) can be performed as necessary. The overaging treatment is a process of maintaining the temperature at the end of quenching for a certain period of time. The overaging treatment does not require any additional treatment and can be considered as a type of air cooling treatment. The overaging treatment has the effect of improving the shape quality by homogenizing the coil in the width direction and length direction of the coil. For this reason, the overaging treatment can be performed for 200 to 800 seconds.

[0069] Plating A plating layer can be formed through a plating process after the annealing. The plating can be performed by a hot-dip plating method in which a plating bath is provided during annealing and the steel sheet is dipped in a hot-dip plating solution, or by electroplating with an electrolyte after annealing. LME occurring during spot welding can occur when molten zinc is present, and is therefore unrelated to the manufacturing method of the plated steel sheet. The plating conditions are not particularly limited as long as they are generally known in the technical field to which the present invention pertains. EXAMPLES

[0070] Hereinafter, the present invention will be described in detail with reference to the examples. It is obvious that the following examples can be modified in various ways by those skilled in the art without departing from the scope of the present invention. The following examples are provided for the purpose of understanding the present invention, and the scope of the present invention should not be limited to the following examples, but should be determined by the claims below as well as equivalents thereto.

[0071] (Example) After producing steel slabs having the alloy composition shown in Table 1 below (units are weight %, and the remainder not shown in Table 1 is Fe and unavoidable impurities), each steel slab was heated at 1200°C for 1 hour, and then the finish rolling temperature was set to the conditions in Table 2 below so that the temperature at the center of the material was 800 to 920°C, and a process of spraying water on the surface during finish rolling was applied.

[0072] The produced hot-rolled steel sheet was cooled at a cooling rate of 0.1° C. / s and coiled at 650° C. Thereafter, the coiled hot-rolled steel sheet was cold-rolled at a rolling reduction of 40% and 80% to produce a cold-rolled steel sheet.

[0073] The manufactured cold-rolled steel sheets were heated to an annealing temperature in the range of 730 to 860°C, and heat treated under the annealing temperature conditions in Table 2. The annealing heat treatment was performed in the heating zone (HS), soaking zone (SS), slow cooling zone (SCS), rapid cooling zone (RCS), and overaging zone (OAS) in Figure 1, with the temperatures at each stage shown in Table 2. Meanwhile, slow cooling (SCS section in Table 2) was performed at an average cooling rate of 3°C / s, and rapid cooling (RCS section in Table 2) was performed at an average cooling rate of 20°C / s.

[0074] On the other hand, in order to evaluate the above-mentioned LME properties, the steel sheet surface was electroplated to form a zinc plating layer having a thickness of 5 to 7 μm.

[0075] [Table 1]

[0076] [Table 2]

[0077] The microstructure of each of the steel sheets manufactured by the above method was observed, and the mechanical properties and plating properties were evaluated. The results are shown in Table 3 below.

[0078] At this time, the tensile test for each test piece was carried out by taking a JIS No. 5 size tensile test piece in the direction perpendicular to the rolling direction and then carrying out the tensile test at a strain rate of 0.01 / s.

[0079] To observe the structure of the steel sheets manufactured above, each fraction was measured using a SEM and an image analyzer after nital etching. Meanwhile, the depth of the healthy part of the surface layer of the steel sheets manufactured above was measured using an optical microscope. For LME, spot welding was performed under the same conditions, and then the spot weld was cut and the cross section was observed using an optical microscope to confirm whether or not cracks had occurred in the surface layer due to LME.

[0080] [Table 3]

[0081] In Table 3 above, YS stands for yield strength, TS stands for tensile strength, and the presence or absence of LME was determined by observing cracks formed when the plated zinc melted during spot welding and penetrated into the grain boundaries of the base material.

[0082] As shown in Tables 1 to 3, Examples 1 to 3 of the present invention, which satisfy all of the requirements of the present invention, can ensure excellent spot weldability by preventing cracks due to LME during spot welding while ensuring excellent physical properties. Figure 2 shows the surface layer of Example 1 of the present invention, and it can be confirmed that a healthy layer has been formed.

[0083] Comparative Examples 1, 2, and 4 to 6 were manufactured by a conventional process without water cooling during hot rolling, and therefore no healthy layer was formed in the surface layer, and the steel was sensitive to LME during spot welding, resulting in the formation of defects. In addition, when the cold reduction rate is low and the annealing temperature is low, ferrite recrystallization is insufficient, and austenite is formed, ensuring strength, but there is a problem of low elongation. In particular, FIG. 3 is a photograph of the microstructure of the surface layer of Comparative Example 1, and it can be seen that no healthy layer is formed in the surface layer.

[0084] In Comparative Examples 3 and 7, water was injected during hot rolling to form a healthy ferrite layer on the surface, and no LME cracks were observed. However, there were problems in that the reduction rate was low, recrystallization was slow in the heating section, and the fraction of the hard phase was excessively large, resulting in low elongation.

[0085] In Comparative Example 8, water was sprayed during hot rolling to form a healthy ferrite layer (healthy layer) on the surface, and no LME cracks were observed. It was confirmed that the elongation was deteriorated due to the high internal hard phase fraction caused by cold rolling at a high reduction rate and annealing at a high continuous annealing temperature exceeding Ac1+30°C.

[0086] Comparative Examples 9 to 11 were manufactured by a conventional process without water cooling during hot rolling, so that a sound layer was not formed in the surface layer, and defects were formed due to sensitivity to LME during spot welding. In addition, cold rolling was performed at a high reduction rate, but the continuous annealing temperature exceeded Ac1+30°C, so the internal hard phase fraction was high and the elongation was deteriorated.

Claims

1. In weight percent, C: 0.05-0.10%, Si: 0.3% or less (excluding 0), Mn: 2.0-2.5%, Ti: 0.05% or less (excluding 0), Nb: 0.1% or less (excluding 0), Cr: 1.5% or less (excluding 0), P: 0.1% or less, S: 0.01% or less, and the remainder including Fe and inevitable impurities, The microstructure at 1 / 4 of the steel plate thickness (t) contains 65 to 85% soft phase by area fraction, with the remainder being hard phase. A high-strength, highly formable steel plate having excellent spot weldability, comprising a sound layer in a surface layer portion of the steel plate, the sound layer having a thickness of 5 to 50 μm.

2. The high-strength, highly formable steel plate having excellent spot weldability according to claim 1, wherein the healthy layer is a columnar ferrite layer having a crystal grain size of 6 to 20 μm.

3. 2. The high-strength, highly formable steel plate having excellent spot weldability according to claim 1, wherein the soft phase includes, in terms of area fraction, 60% or more of recrystallized ferrite and 5% or less of unrecrystallized ferrite.

4. 2. The high-strength, highly formable steel plate having excellent spot weldability according to claim 1, wherein the hard phase comprises a martensite structure or a mixed structure in which martensite is mixed with a small amount of bainite.

5. The high-strength, highly formable steel plate having excellent spot weldability according to claim 1 , wherein the aspect ratio of the hard phase is 1.2 or less.

6. The high-strength, highly formable steel sheet having excellent spot weldability according to claim 1 , further comprising a plating layer on the surface of the steel sheet.

7. The high-strength, highly formable steel plate having excellent spot weldability according to claim 1, wherein the steel plate has a tensile strength (TS) of 780 MPa or more and an elongation (El) of 18% or more.

8. a step of heating a steel slab containing, in weight percent, C: 0.05-0.10%, Si: 0.3% or less (excluding 0), Mn: 2.0-2.5%, Ti: 0.05% or less (excluding 0), Nb: 0.1% or less (excluding 0), Cr: 1.5% or less (excluding 0), P: 0.1% or less, S: 0.01% or less, the remainder being Fe and unavoidable impurities, in a temperature range of 1100-1300°C; hot rolling the heated steel slab and hot rolling the steel slab while cooling the steel slab so that the surface temperature of the steel slab is Ar3 or less for a predetermined time during the finish hot rolling; coiling and cooling the hot-rolled sheet; cold rolling the cooled hot rolled sheet at a rolling reduction of 70 to 90%; After the cold rolling, heating to a temperature range of Ac1 to Ac1+30° C. and maintaining the temperature; and cooling the cold-rolled steel sheet slowly to a temperature range of 650 to 700° C. at an average cooling rate of 1 to 10° C. / s, and then quenching the cold-rolled steel sheet to a temperature range of 300 to 580° C. at an average cooling rate of 5 to 50° C. / s; A method for producing a high-strength, highly formable steel plate having excellent spot weldability, comprising:

9. The method for producing a high-strength, highly formable steel plate having excellent spot weldability according to claim 8, wherein the temperature of the material during the finish hot rolling is Ar3 to 1000°C.

10. The method for producing a high-strength, highly formable steel plate having excellent spot weldability according to claim 8, wherein the coiling is performed at 400 to 700°C, and the coiling is cooled at a cooling rate of 0.1°C / s or less.

11. The method for producing a high strength, highly formable steel plate having excellent spot weldability according to claim 8, further comprising the step of overaging for 200 to 800 seconds after the quenching.

12. The method for producing a high strength, highly formable steel plate having excellent spot weldability according to claim 8, wherein the surface is cooled by spraying water at least once between rolling passes during the finish hot rolling.

13. The method for producing a high-strength, highly formable steel plate having excellent spot weldability according to claim 8, further comprising the step of forming a plating layer.

Citation Information

Patent Citations

  • Environmentally friendly high-strength, highly formable steel plate and its manufacturing method

    JP2024540919A

  • Steel plate with excellent resistance to spot weld fracture and manufacturing method thereof

    JP6524810B2

  • High-strength steel plate, high-strength member and method for manufacturing the same

    JP6947327B2

  • Steel sheet

    WO2020218572A1

  • Steel sheet and method for manufacturing same

    WO2020225936A1